Cerebrospinal Fluid-Venous Fistulas: A Systematic Review and Examination of Individual Patient Data. Issue 5 (13th January 2021) - Shlobin, Nathan A; Shah, Vinil N; Chin, Cynthia T; Dillon, William P; Tan, Lee A
Abstract: BACKGROUND: Spontaneous intracranial hypotension (SIH) is usually caused by a spinal cerebrospinal fluid (CSF) leak. CSF-venous fistula is an underdiagnosed cause of spinal CSF leak, as it is challenging to identify on myelography. OBJECTIVE: To review existing literature to summarize common presentations, diagnostic imaging modalities, and current treatment strategies for CSF-venous fistulas. METHODS: We conducted a systematic review using PubMed, Embase, Scopus, and Web of Science databases to identify studies discussing CSF-venous fistulas. Titles and abstracts were screened. Studies meeting prespecified inclusion criteria were reviewed in full. RESULTS: Of 180 articles identified, 16 articles met inclusion criteria. Individual patient data was acquired from 7 studies reporting on 18 patients. CSF-venous fistula most frequently presented as positional headache. Digital subtraction myelography provided greatest detection of CSF-venous fistula in the lateral decubitus position and detected CSF-venous fistula in all individual patient cases. Dynamic computed tomography (CT) myelogram enabled detection and differentiation of CSF-venous fistulas from low-flow epidural leaks. The majority of fistulas were in the thoracic spine and slightly more common on the right. Epidural blood patch (EBP) provided temporary or no relief in all individual patients. Resolution or improvement of clinical symptoms and radiologic normalization were observed in all surgically treated patients. CONCLUSION: Although rare, CSF-venous fistula is an important cause of spinal CSF leak contributing to SIH. Dynamic CT myelogram and digital subtraction myelography, particularly in the lateral decubitus position, are the most accurate and effective diagnostic imaging modalities. EBPs often provide only transient relief, while surgical management is preferred.